Analysis on the Effective Leadership Style and Human Resource management Roles in Operational and Commerce Directorates in PT Kereta Api Indonesia Head Office Based on Organizational Culture Asessment Instrument - Waskitadi, Mahatma; Tjakraatmadja, Jann Hidajat (Journal of Business and Management, 2015)
Abstract. PT KAI had changed the vision to become the railways services provider that focus to customer services and fulfill the stakeholder expectations. The vision were translated in many programs such as the expansion in asset and business units. Every functional of PT KAI also have their own performance targets to reach the company vision.However, the change in their performances targets should be assured to have the sustainable benefit to the company. Empirical research has produced an impressive array of findings demonstrating the importance of culture to enhancing organizational performance (for reviews, see cameron and ettington, 1988;1990; and trice and beyer, 1993). In this research, the researcher want to analyze the condition of PT KAI in culture perspective. This research could be the refference for PT KAI management to understand the condition of PT KAI culture that currently present and the preffered culture that the employees. With that findings, the researcher could suggest the effective leadership style and human resource management roles for the organizations. The researcher choose commerce and operation directorate as the objects of the research because it was the core function that can support the company growth.The methods which is used in this research is organizational cultural assestment instrument (ocai) which is invented by cameron & quinn (1999). The result of the anaysis would show the tendency of PT KAI’s commerce and operation directorate organizational culture.The result shows that both directorates should emphasize the market and adhocracy cultures.Key words: Organization, Corporate, Cilture, OCAI, PT KAI.